#TITLE_ALTERNATIVE# - ADI NUGROHO (NIM 13204179), RAMADHAN
Transient stability is the ability of the system to be stable when disturbances occur. Disturbances in power system are short circuit in transmission line, loss of unit generator and loss of loads on the system. The important things that in the transient stability analysis is how the system's ability to respond to disturbances that occurs in the system. Three-phase short circuit in transmission line is related to the critical clearing time of the fault. Generator will be lost of synchronism if transient stability limit is much smaller than the relay settings of transmission line. Loss of a unit generator related to the amount of power is lost from system and the impact of another generator that interconnected to system. In this simulation shows in 2011, Circuit Breaker clearing time still under Critical Clearing Time although in some lines marginal time is small.